Natural occurrence of the entomopathogenic genus Pandora on spittlebug pests of crops and pastures in Argentina - Foieri, Alvaro (2018)
The natural occurrence of entomophathogenic fungi infecting spittlebugs (Hemiptera: Cercopidae) considered serious pests to pasture grasses and crops in Argentina was investigated during summer˗autumn (December to May) from 2013 to 2016. Adults and nymphs of spittlebugs were collected from Sorghum halepense and Setaria parviflora var. parviflora in San Miguel de Tucumán, Tucumán province. The entomopathogenic fungal species were characterized on the basis of morphological keys and molecular techniques. Microscopic characters were described from material mounted in lactophenol/aceto‐orcein (1% w/v), and the amplification of the fungal SSU rDNA was carried out using the universal primers nu‐SSU‐0021‐5′ and nu‐SSU‐1780‐3′. Summarized information about occurrence of fungal infections on spittlebugs populations is provided. This study reports for the first time the occurrence of the genus Pandora infecting adults of the economically important spittlebugs Deois (Deois) mourei, D. (D.) knoblauchii, Isozulia christenseni christenseni and Notozulia entreriana from Argentina expanding the host range and geographical distribution of entomophthoralean fungi.